The Policy of Kuningan District Regional Government in The Efforts to Prevent Human Trafficking - Haris Budiman (Universitas Kuningan, 2018)
The era of regional autonomy has made regions strive to utilize their potential for the sake of community’s welfare. Yet, the limited job opportunities cause the job seekers to work abroad which results in various legal cases, including human trafficking. The purpose of this research is to analyze the regulations on human trafficking, the factors causing human trafficking, and the role of regional government in preventing human trafficking. The research method used was non-doctrinal. The results showed that human trafficking has been regulated in various regulations, but in practice, the regulations are not well implemented because of various factors, including economic, social, and cultural factors. Moreover, the policy of Kuningan District Regional Government in the efforts to prevent human trafficking is limited to the forming of Integrated Service Center for Empowering Women and Children (P2TP2A) which in its implementation has not run optimally due to limited funds and participation from the community. Era otonomi daerah menjadikan daerah berupaya untuk memanfaatkan potensi yang dimilikinya dalam rangka mensejahterakan masyarakat. Akan tetapi keterbatasan lapangan kerja menyebabkan tingginya para pencari kerja untuk bekerja di luar negeri, sehingga menimbulkan berbagai kasus hukum, diantaranya perdagangan manusia. Rumusan masalah: bagaimana pengaturan tentang perdagangan manusia, faktor-faktor apa yang menjadi penyebab terjadinya perdagangan manusia, serta bagaimana peran pemerintah daerah dalam mencegah terjadinya Perdagangan manusia. Metode penelitian yang digunakan bersifat non doktrinal dengan pendekatan yuridis empiris. Pengaturan perdagangan manusia telah diatur dalam berbagai perundang-undangan namun dalam pelaksanaannya tidak berjalan dengan optimal karena ada faktor yang mempengaruhi. Faktor-faktor tersebut antara lain faktor ekonomi, faktor sosial dan faktor budaya. Kebijakan Pemerintah Daerah Kabupaten Kuningan dalam upaya mencegah perdagangan manusia baru sebatas membentuk Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A). yang dalam pelaksanaannya belum berjalan optimal karena